Caracterização física e de secagem de sementes de embaúba (Cecropia glaziovii Snethlage) - Felizardo, Marcos Paulo (2014)
The drying of seeds of the pioneer species Cecropia glaziovii Snethlage is motivated due to its restoration characteristics of heterogeneous degraded forests. In this work the main goal is the physical and drying characterization of Cecropia glaziovii seeds in batch fluidized bed, as well as the physiological quality. The dimensions and shapes of seeds were obtained by image analysis, assessing the reproducibility of these measures for in natura samples and those classified by sieving. The drying characterization in fluidized bed drying was performed, with initial fixed bed heights of 3 and 5 cm, with air temperature (40 ± 2)°C and drying air velocity (1.0 ± 0.3) m/s. It was noted that the dimensions and shapes of seeds classified by sieving have higher reproducibility than the in natura ones. Therefore, the seeds retained on the 20 mesh sieve were used for the drying characterization. By using the moisture ratio as a function of time, it could be seen that the mixture in the fluidized bed was homogeneous, as the variation between the bed heights of 3 and 5 cm was negligible. Based on the dimensionless drying rate as a function of moisture ratio, only the decreasing rate period was observed. It was also found that the seeds constitute a porous and hygroscopic particulate system in the conditions used in this study. Therefore, samples with statistical reproduction of sizes and shapes were obtained by physical characterization, and for these seeds, drying characterization was carried out, obtaining the classification of the particulate system as porous and hygroscopic medium without reporting constant drying rate period. The germination index of Cecropia glaziovii seeds was 77%, this value is consistent with government reforestation programs.